Human resource transaction management system security optimize using multithreading with blowfish Algorithm - Krishna, Ashu; Rath, Satyajit; Kumar, Madhurendra (Gyan Management Journal, 2024)
Today HRMS (Human resource management system) application around data transmitting from one place to another is challenging and doing this with real-time data is even more difficult to service time minimize and secure. In this paper using Blowfish algorithm with multithreading technology we will solve the waiting time using dis tributed data streaming platform. This approach will become ideal to daily life where each and every user get services in optimize way with secure direction.